Lichen Planus Pemphigoides: From Lichenoid Inflammation to Autoantibody-Mediated Blistering - Hübner, Franziska; Langan, Ewan A.; Recke, Andreas (Frontiers in Immunology, 2019)
Lichen planus pemphigoides (LPP) is a very rare autoimmune sub-epidermal blistering disease associated with lichenoid skin changes. Initially thought to be a mere variant of more common inflammatory dermatoses, particularly Bullous Pemphigoid (BP) or Lichen Planus (LP), a growing body of evidence suggests that it is a disease entity in its own right. In common with a range of autoimmune blistering diseases, including BP, pemphigoid gestationis (PG), mucous membrane pemphigoid (MMP) and linear IgA dermatosis (LAD), a key feature of the disease is the development of autoantibodies against type XVII collagen (COL17). However, accurately establishing the diagnosis is dependent on a careful correlation between the clinical, histological and immunological features of the disease. Therefore, we present an up to date summary of the epidemiology and etiopathogenesis of LPP, before illustrating the predisposing and precipitating factors implicated in the development of the disease. In addition to a selective literature search, we compare reports of potential drug-induced cases of LPP with pharmacovigilance data available via OpenVigil. We subsequently outline the cardinal clinical features, important differential diagnoses and current treatment options. We conclude by demonstrating that an improved understanding of LPP may not only lead to the development of novel treatment strategies for the disease itself, but may also shed new light on the pathophysiology of more common and treatment-refractory autoimmune blistering diseases.